Social media communication of public institutions. Case study: Representation of the European Commission in Romania - Rus, Mihaela; Tasențe, Tănase; Cămară, Valentina (Technium Social Sciences Journal, 2021)
With the development of social networks and their becoming as the main means of informing citizens about the activities of local, central and European public administration, more and more institutions have synchronized their institutional communication strategy with the functioning mechanisms and characteristics of Social Media. At the same time, in the age of social networks, concepts for authority and control of the public message have been reconfigured, and most public institutions have understood that in Social Media (Facebook, Twitter, LinkedIn, Instagram, Youtube, etc.), institutions do not have control over the message, but the essential role in the dissemination and control of the message is played by the online public.